Impact of mild to severe hemophilia on education and work by US men, women, and caregivers of children with hemophilia B: The Bridging Hemophilia B Experiences, Results and Opportunities into Solutions (B‐HERO‐S) study. (April 2017) - Cutter, Susan; Molter, Don; Dunn, Spencer; Hunter, Susan; Peltier, Skye; Haugstad, Kimberly; Frick, Neil; Holot, Natalia; Cooper, David L.
Abstract: The psychosocial impact of hemophilia on work was recently investigated in the Hemophilia Experiences, Results and Opportunities (HERO) study. The findings revealed that hemophilia had an impact for adults with moderate/severe hemophilia and caregivers of children with hemophilia. HERO did not specifically evaluate impact on education in adults/children with mild/moderate hemophilia or the impact on employment of spouses/partners of caregivers of affected children. The Bridging Hemophilia B Experiences, Results and Opportunities into Solutions (B‐HERO‐S) study evaluated the impact of hemophilia on the lives of adult men/women with mild‐severe hemophilia B and caregivers of boys/girls with hemophilia B and their spouses/partners. Many adults with hemophilia B (94%) reported that hemophilia had a negative effect on their ability to complete a formal education, often attributed to the inability to attend or concentrate in school as a result of hemophilia‐related bleeding or pain. Most adults with hemophilia B (95%) and caregivers/partners (89%/84%) indicated that hemophilia had a negative impact on employment. Most adults with hemophilia were employed (81%), with construction/manufacturing (35%) as the most frequently reported industry; many worked in jobs requiring manual labor (39%). Of those unemployed, 62% never worked, and those who stopped working reported that they left the workforce due to financial issues (59%), including insurance coverage/co‐pays, or hemophilia‐related issues (55%). Nearly one‐third of caregivers voluntarily left the workforce to care for children with hemophilia. These results suggest a need to focus more effort on career counseling for adults with hemophilia B and caregivers of affected children, especially around mild/moderate hemophilia, as this population may not be as well informed regarding potential impact in school and the workplace.